2020
DOI: 10.3389/fmicb.2020.01772
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Responses to Simulated Salinization and Desalinization in the Sediments of the Qinghai–Tibetan Lakes

Abstract: Uncovering microbial response to salinization or desalinization is of great importance to understanding of the influence of global climate change on lacustrine microbial ecology. In this study, to simulate salinization and desalinization, sediments from Erhai Lake (salinity 0.3-0.8 g/L) and Chaka Lake (salinity 299.3-350.7 g/L) on the Qinghai-Tibetan Plateau were transplanted into different lakes with a range of salinity of 0.3-299.3 g/L, followed by in situ incubation for 50 days and subsequent geochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 73 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…The Chaka (CK) Lake is located on the eastern edge of the Qaidam Basin, and the lake is characterized as magnesium sulfate type. , The annual average temperature is 3.5 °C, the lowest monthly temperature at −12.4 °C is in January, and the highest at 14.4 °C is in July. The annual average precipitation is 198 mm, and the annual average evaporation is 2074 mm. , During the dry season, little brines remain, and during the wet season (May to September), the lake area is ∼116 km 2 with an average depth of 10 cm.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…The Chaka (CK) Lake is located on the eastern edge of the Qaidam Basin, and the lake is characterized as magnesium sulfate type. , The annual average temperature is 3.5 °C, the lowest monthly temperature at −12.4 °C is in January, and the highest at 14.4 °C is in July. The annual average precipitation is 198 mm, and the annual average evaporation is 2074 mm. , During the dry season, little brines remain, and during the wet season (May to September), the lake area is ∼116 km 2 with an average depth of 10 cm.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…In saline soils, the addition of plant residues increases microbial activity and biomass temporarily; as a result, microbial activity and biomass return to values similar to those in the unamended soils [5]. Similarly, previous studies have reported that application of plant residues could mitigate the effects of salinity on soil microbial properties under laboratory conditions [13] and also could improve soil fertility [48]. In fact, the addition of plant residues is a widely used practice to enhance soil fertility [39].…”
Section: Introductionmentioning
confidence: 90%
“…This can be attributed to the production of specific compounds and metabolites as well as the improvement of the soil fertility to the less decrease of microbial biomass in bacterial and fungal treatments under stress condition [16]. It seems that increased soil microbial biomass and their activity in soil treated with wheat residues could be due to the availability of easily degradable materials that provided nutrients and a suitable substrate for microorganisms [10,13].…”
Section: Soil Biochemical Properties In Saline Soil Treated With Whea...mentioning
confidence: 99%
“…For the lowest trophic levels (e.g., bacteria, fungi), changes in their communities either in the species composition and/or their activity induced by FS can modulate ecosystem functions and drive processes related to GHG production. Denitrification [69,111], methane production [112], but also dissolved organic carbon, detrital processing, and decomposition [39,68] are key aspects linked to microbial activity that need further attention. Molecular methods used to assess microbial diversity, linking it with functionality, can help to analyse these processes [76].…”
Section: Open Accessmentioning
confidence: 99%